2022
DOI: 10.1088/1361-6668/ac86ac
|View full text |Cite
|
Sign up to set email alerts
|

Formation and propagation of cracks in RRP Nb3Sn wires studied by deep learning applied to x-ray tomography

Abstract: This paper reports a novel non-destructive and non-invasive method to investigate crack formation and propagation in high-performance Nb3Sn wires by combining X-Ray tomography and deep learning networks. The next generation of high field magnet applications relies on the development of new Nb3Sn wires capable to withstand the large stresses generated by Lorentz forces during magnets operation. These stresses can cause a permanent reduction of the transport properties generated by residual deformation of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The study pointed out that the irreversible degradation of the critical current under the transverse stress of 180 MPa is mainly caused by the plastic deformation of the copper matrix, and the effect of filament fracture becomes obvious above this stress. Bagni et al [42,43] investigated sub-elements voids, crack formation and propagation in Nb 3 Sn wires by combining x-ray micro-tomography and machine learning. All these studies significantly contribute to the understanding of strain sensitivity and irreversible degradation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The study pointed out that the irreversible degradation of the critical current under the transverse stress of 180 MPa is mainly caused by the plastic deformation of the copper matrix, and the effect of filament fracture becomes obvious above this stress. Bagni et al [42,43] investigated sub-elements voids, crack formation and propagation in Nb 3 Sn wires by combining x-ray micro-tomography and machine learning. All these studies significantly contribute to the understanding of strain sensitivity and irreversible degradation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…An independent confirmation of the dominant role of residual stresses on the degradation of I c came from a study combining x-ray tomography and deep learning Convolutional Neural Networks, reported in [33]. Tomography images were taken at the European Synchrotron Radiation Facility on the RRP wire sample at 0.7 mm extracted from the I c vs transverse stress probe at the end of the experiment after the final unload from 240 MPa.…”
Section: Resultsmentioning
confidence: 96%
“…The wire volume examined by tomography corresponds to a scan length of about 1.5 mm. More details about the methods of detection and image recognition are reported in the [29,33,34]. Only very few cracks are present in the examined sample after unload from 240 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the voids need to be considered in a wire mechanical FE model to reproduce the wire properties, faithfully. ML and CNN can detect and separate the voids from the other components allowing the 3D reconstruction of the wire's internal structures (see figure 24) [133,134].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%